Numerical and Experimental Investigation of Irradiance Profiles on Suspended Particles in a Flat Disk Photoreactor for Hydrogen Generation - Diaz-Robles, L (Elsevier Ltd, 2023)
Regarding sustainable energy alternatives, the present work evaluates hydrogen production using suspended particles exposed to an irradiance of 247 W/m2. A 1.0 L flat disk photoreactor (FDP) was designed for evaluating agitation speeds of 100, 175, and 250 RPM, and particle concentrations of 0.5, 1.0, and 2.0 g/L. Through CFD-assisted, a non-conformal meshing of 551,000 polyhedral elements was created, coupling Volume of Fluids, Discrete Particle Modelling, and Discrete Ordinates Model methods. Transient simulation shows a maximum particle homogenization of 84 % at 0.5 g/L and 250 RPM, and a maximum average exposure profile of 140 W/m2 for 27% of the particles with an initial loading of 1.0 g/L at 250 RPM. Effective concentration in the FDP was measured, determining an accuracy of 84.35% and 71.32%, respectively, concerning the model used in the simulation. It is concluded that the FDP developed provides good semiconductor behavior for an effective hydrogen production process. © 2023 Elsevier Ltd